Competing interactions in the XYZ model - Arlego, Marcelo José Fabián (2003)
We study the interplay between an XY anisotropy γ, exchange modulations, and an external magnetic field along the z direction in an XYZ chain using bosonization and Lanczos diagonalization techniques. We find an Ising critical line in the space of couplings which occur due to competing relevant perturbations that are present. More general situations are also discussed.